2006
DOI: 10.1111/j.1600-6143.2005.01221.x
|View full text |Cite
|
Sign up to set email alerts
|

HLA Type-Independent Method to Monitor Polyoma BK Virus-Specific CD4+ and CD8+T-Cell Immunity

Abstract: (Re)activation of quiescent viral diseases is a major problem in immunosuppressed transplant patients. Polyoma BK virus-associated nephropathy (PVAN) caused by active polyoma BK virus (BKV) infection became a main reason for graft loss in kidney transplantation. After diagnosis, most transplant centers react by reducing immunosuppression (IS) to allow the immune system to control the infection. However, the impact of reduced IS on BKV immunity is not well researched. Here we present an HLA type-independent met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
40
2

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(49 citation statements)
references
References 16 publications
(33 reference statements)
7
40
2
Order By: Relevance
“…Mannon et al (50) found that the RNA transcriptional profiles that were associated with BKV nephropathy indicated a more intense CD8 functional response and more profibrotic response than acute cellular rejection. Hammer et al (69) found that recipients with viral loads Ͼ250,000 copies/ml had detectable BKV-specific CD4 ϩ T cells in peripheral blood, but only the two recipients with BKV-specific CD8 ϩ T cells Ͼ0.1% lost their allografts. The specificity of the cellular response may also be detrimental.…”
Section: Immunologymentioning
confidence: 99%
“…Mannon et al (50) found that the RNA transcriptional profiles that were associated with BKV nephropathy indicated a more intense CD8 functional response and more profibrotic response than acute cellular rejection. Hammer et al (69) found that recipients with viral loads Ͼ250,000 copies/ml had detectable BKV-specific CD4 ϩ T cells in peripheral blood, but only the two recipients with BKV-specific CD8 ϩ T cells Ͼ0.1% lost their allografts. The specificity of the cellular response may also be detrimental.…”
Section: Immunologymentioning
confidence: 99%
“…It has lately been hypothesized that development of BKV-capsid protein (VP1)-specific CD8 T-cell response in allograft recipients with BKV plasma replication may be associated with negative PVAN outcome (12). However, prospective data on BKV-specific immunity are lacking in patients with positive BKV viremia or PVAN, and, therefore, the role of BKV-specific T cells on the course of BKV infection and pathogenesis of PVAN remains to be clarified.…”
Section: Introductionmentioning
confidence: 99%
“…Hammer and colleagues report on BKV-specific T-cell responses in peripheral blood mononuclear cells (PBMC) of 15 viremic kidney transplant recipients (1). After stimulation with overlapping peptides spanning the viral capsid protein VP1, interferon-c (IFNc )-producing CD4+ T cells were observed in 7 patients (47%), including 2 patients (13%) with a CD8+ T-cell response.…”
Section: Bkv Replication and Cellular Immune Responses In Renal Transmentioning
confidence: 99%